Legends of Zita the spacegirl - Hatke, Ben (New York : First Second, 2012)
Zita is determined to find her way home to Earth, but her exploits have made her an intergalactic megastar, and as her true self is eclipsed by her public persona, she faces a robot doppelganger, and is unsure of who she can trust.
Keywords: Heroes -- Fiction; Fame -- Fiction; Robots -- Fiction; Extraterrestrial beings -- Fiction; JUVENILE FICTION / Comics & Graphic Novels / General; JUVENILE FICTION / Science Fiction; JUVENILE FICTION / Action & Adventure / General; Heroes and heroines -- Fiction; Fame -- Fiction; Robots -- Fiction; Extraterrestrial beings -- Fiction; Graphic novels; Science fiction graphic novels; Science fiction